Electrocupuncture combined rehabilitation therapy for upper limb spasticity after stroke: A protocol for systematic review and meta-analysis. Issue 47 (24th November 2021) - Lou, Huijuan; Li, Zhanxin; Pang, Tingting; Zhang, Xinxin; Meng, Meng; Yang, Kang; Zhang, Hongshi; Wang, Yufeng; Cong, Deyu
Abstract: Background: The purpose of this study was to evaluate the effectiveness and safety of electroacupuncture combined with rehabilitation in the treatment of spasticity after stroke. Methods: To collect relevant literature, we will research following databases: Medicine, PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure, Wan-Fang Database, Chongqing VIP Chinese Science and Technology Periodicals Database and China Biomedical Database; the time is from its creation to May 2021, and the language is limited to Chinese and English. In addition, we will retrieve other literature resources, including the Chinese Clinical Trial Register and conference papers. Two reviewers will independently complete the literature screen and data extraction, and quality assessment of the included studies will be independently completed by two other researchers. The primary outcomes included the Modified Ashworth scale (MAS) and the simplified Fugl-Meyer Assessment scale (SFMA). The Modified Barthel Index (MBI), the China Stroke Scale (CSS), and adverse reactions as secondary outcomes were assessed. RevMan V.5.4.1 software will be used for meta-analysis, and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) will be used to assess the quality of evidence. Results: This systematic review will provide a high-quality synthesis to evaluate the efficacy and safety of electroacupuncture combined with rehabilitation therapy in the treatment of upper limb spasticity after stroke, providing a reference for the safe and effective treatment of upper limb spasm after stroke. Conclusion: This study provides evidence that electroacupuncture combined with rehabilitation therapy is effective. Ethics and dissemination: The protocol of the systematic review does not require ethical approval because it does not involve humans. This article will be published in peer-reviewed journals and presented at relevant conferences. Systematic review registration: INPLASY202160005.